Discounting of food and water in rats shows trait‐ and state‐like characteristics. Issue 2 (8th February 2021) - Haynes, Jeremy M.; Galizio, Ann; Frye, Charles C. J.; Towse, Caroline C.; Morrissey, Kailey N.; Serang, Sarfaraz; Odum, Amy L.
Abstract : Delay discounting is the loss in value of an outcome as a function of its delay. The present study focused on examining a trait‐like characteristic of delay discounting in a preclinical animal model. Specifically, we were interested in whether there was a positive relation between discounting of 2 different outcomes in rats. That is, would rats that discount delayed food steeply also discount delayed water steeply? In addition, we examined how session‐to‐session variability in discounting could be attributed to differences between subjects (trait variability) and to differences within subjects (state variability). Finally, we measured discounting from early‐ to mid‐adulthood, allowing us to examine changes in discounting as a function of age. Overall, we found a moderate, positive correlation between discounting of food and discounting of water in rats, providing further evidence that the relative consistency with which individuals discount different outcomes is a trait‐like characteristic. In addition, we found a high degree of within‐subject variability in discounting, indicating strong state‐like differences from session to session. Finally, overall, discounting decreased as a function of age; however, individual‐subject data showed variability in how discounting changed across time. Overall, our results show that differences in delay discounting between individuals reflect variability in both trait‐ and state‐like characteristics.